Pemanfaatan Limbah Cangkang Kerang Simping (Amusium Pleuronectes) Sebagai Katalisator Pada Proses Carburizing - Muhamad Juniardi; Ramli, Ramli; Zulfitriyanto, Zulfitriyanto (Jurnal Inovasi Teknologi Terapan, 2024)
Simping clam’s a type of waste that is rarely used. The high levels of calcium carbonate in simping shells enable them to be used as a catalyst in the carburizing process. This research aimed to determine the effect of simping clam shell powder as a catalyst in the carburizing process on the hardness and impact strength values of ST 42 steel. This research used an experimental method by varying the percentage of simping clam shell powder: 0%, 10%, 20%, 30%, and coconut shell activated charcoal powder: 100%, 90%, 80%, and 70%, against ST 42 steel with variations in carburizing time: 3 hours, 6 hours, and 9 hours using a temperature of 900°C. The tests carried out were rockwell hardness tests and charpy impact tests according to ASTM E23 standards. From the test results, it was obtained that good hardness and impact strength values were obtained in 3 hours, the percentage was 30% with an average hardness value of 34.02 HRC and an impact value of 0.279 joules/mm2, in 6 hours the percentage was 30% with an average hardness value of 38. 92 HRC and an impact value of 0.229 joules/mm2, a time of 9 hours with a percentage of 30% an average hardness value of 43.68 HRC and an impact value of 0.179 joules/mm2. So by increasing the carburizing time, the hardness increases. The longer the carburizing time, the higher the percentage of simping clam shell powder used. This means that simping clam shell powder  functions as a catalyst.